New information on Brindabellaspis stensioi Young, 1980, highlights morphological disparity in Early Devonian placoderms - King, Benedict (R Soc Open Sci, 2018)
Acid-prepared specimens of the placoderm Brindabellaspis stensioi (Early Devonian of New South Wales, Australia) revealed placoderm endocranial anatomy in unprecedented detail. Brindabellaspis has become a key taxon in discussions of early gnathostome phylogeny, and the question of placoderm monophyly versus paraphyly. The anterior orientation of the facial nerve and related hyoid arch structures in this taxon resemble fossil osteostracans (jawless vertebrates) rather than other early gnathostomes. New specimens of Brindabellaspis now reveal the previously unknown anterior region of the skull, including an exceptionally elongate premedian bone forming a long rostrum, supported by a thin extension of the postethmo-occipital unit of the braincase. Lateral overlap surfaces indicate an unusual anterior position for the jaws. Digital rendering of a synchrotron radiation scan reveals a uniquely specialized ethmoid commissure sensory canal, doubled back and fused into a midline canal. The visceral surface of the premedian bone has a plexus of perichondral bone canals. An updated skull roof reconstruction of Brindabellaspis adds to the highly variable dermal skull patterns of the probably non-monophyletic ‘acanthothoracids'. The unusual morphology revealed by the new specimens suggests that the earliest known reef fish fauna contained a diverse range of fishes with specialized ecological roles.